Digital literacy and education: report by country: Portugal - Brites, Maria José (2017)
In the end of the 1990s, the discourse was mostly focused on access to the internet, and terms used were such as ‘info-inclusion’/’info-exclusion’ and ‘info-alphabetisation’ (Missão para a Sociedade da Informação [Mission for Information Society], 1997). During the first decade of the 2000s, it changed to a focus on the spread of broadband and ICT among active population and students, without an emphasis to the dimension of competences or literacy. The agenda was that of integrating ICT in more and more sectors of public life, from education to health and governance (Plano Tecnológico da Educação [Technological Plan for Education] - PTE, 2007).